Painful Unilateral Temporalis Muscle Enlargement: Reactive Masticatory Muscle Hypertrophy - Katsetos, Christos D. (Springer US, 2013)
An instance of isolated unilateral temporalis muscle hypertrophy (reactive masticatory muscle hypertrophy with fiber type 1 predominance) confirmed by muscle biopsy with histochemical fiber typing and image analysis in a 62 year-old man is reported. The patient presented with bruxism and a painful swelling of the temple. Absence of asymmetry or other abnormalities of the craniofacial skeleton was confirmed by magnetic resonance imaging and cephalometric analyses. The patient achieved symptomatic improvement only after undergoing botulinum toxin injections. Muscle biopsy is key in the diagnosis of reactive masticatory muscle hypertrophy and its distinction from masticatory muscle myopathy (hypertrophic branchial myopathy) and other non-reactive causes of painful asymmetric temporalis muscle enlargement.